Histology of the parapapillary region in high myopia - Jonas, Jost B.; Jonas, Shefali B.; Jonas, Rahul A.; Holbach, Leonard; Panda-Jonas, Songhomitra (American Journal of Ophthalmology, 2011)
To examine histomorphometrically the parapapillary region in highly myopic eyes.Retrospective laboratory investigation.We examined a highly myopic glaucomatous group (36 human globes; axial length >26.5 mm) and a non-highly myopic group (28 globes with secondary angle-closure glaucoma; 17 eyes with malignant choroidal melanoma). Using light microscopy, pupil-optic nerve sections were assessed.The length of the scleral flange (sclera between optic nerve border and optic nerve dura mater) increased with axial length (P < .001; correlation coefficient r = 0.70) and decreased with its thickness (P < .001; r = 0.75). In all highly myopic eyes (n = 15) with a distance of >0.5 mm between optic nerve border and beginning of Bruch membrane, the parapapillary region consisted of an elongated parapapillary scleral flange associated with a scleral flange thinning and a retrobulbar cerebrospinal fluid space extended into the retroparapapillary region. The parapapillary retina was composed of retinal nerve fiber layer (or its remnants) only, without elements of any other retinal layer, without underlying Bruch membrane or choroid. These histologic features were not detected in any of the non-highly myopic eyes.Since parapapillary scleral thickness influences the lamina cribrosa biomechanics, the findings may partially explain the increased glaucoma susceptibility in highly myopic eyes. The implications of an absence of Bruch membrane and choroid in the highly myopic parapapillary region, and the implications of the retrobulbar parapapillary extension of the cerebrospinal spinal fluid space for the pathophysiology of the optic nerve head, have to be elucidated.
EVALuna2:21032